Numerical study on the aerodynamic performance of the three-dimensional wing of a jellyfish-like flyer - Meng, Xueguang; Deng, Chengjian; Wang, Dingsheng; Jiang, Shujie (Frontiers in Physics, 2023)
The jellyfish-like flying machine is a new development direction of the future bionic flapping-wing aircraft besides the insect-mimic and bird-mimic Micro Air Vehicles (MAVs). To better understand the underlying fluid mechanisms of the jellyfish-like flyer, we numerically simulated the aerodynamic forces of the three-dimensional flapping wings under different control parameters. The effects of flapping amplitude, vortex wake, up-flight speed as well as wing-wing interaction on aerodynamic performance were investigated. The results show that, at hovering, the mean lift rises rapidly at first and then tends to be stable with the increase of flapping amplitude. The vortex wake can improve the lift at large flapping amplitudes, while it reduces the lift at very small flapping amplitude. With the increase of up-flight speed, the lift decreases. However, the sources of lift reduction are different for different flapping amplitudes. When the two wings flap together and the distance between wings is small enough, the wing-wing interaction can improve the lift by about 15% compared with that of a single wing, but much higher power is required, resulting in lower efficiency. The results of this study provide new insights into the flight mechanism of the jellyfish-like aircraft and have important guiding significance for the design and optimization of the jellyfish-like flying machine.